Virtual reality balance training for elderly: Similar skiing games elicit different challenges in balance training - de Vries, Aijse W.; Faber, Gert; Jonkers, Ilse; Van Dieen, Jaap H.; Verschueren, Sabine M.P. (Gait & posture, 2018)
•The Kinski game elicited larger COM excursions than the Wiiski game.•Participants quickly became more efficient, reducing the challenge to balance especially on the Wiiski game.•For both games smaller COM movement resulted in lower score.•Off the shelf games do not seem optimized for balance training for healthy elderly. Virtual Reality (VR) balance training may have advantages over regular exercise training in older adults. However, results so far are conflicting potentially due to the lack of challenge imposed by the movements in those games. Therefore, the aim of this study was to assess to which extent two similar skiing games challenge balance, as reflected in center of mass (COM) movements relative to their Functional Limits of Stability (FLOS). Thirty young and elderly participants performed two skiing games, one on the Wii Balance board (Wiiski), which uses a force plate, and one with the Kinect sensor (Kinski), which performs motion tracking. During gameplay, kinematics were captured using seven opto-electronical cameras. FLOS were obtained for eight directions. The influence of games and trials on COM displacement in each of the eight directions, and maximal COM speed, were tested with Generalized Estimated Equations. In all directions with anterior and medio-lateral, but not with a posterior component, subjects showed significantly larger maximal %FLOS displacements during the Kinski game than during the Wiiski game. Furthermore, maximal COM displacement, and COM speed in Kinski remained similar or increased over trials, whereas for Wiiski it decreased. Our results show the importance of assessing the movement challenge in games used for balance training. Similar games impose different challenges, with the control sensors and their gain settings playing an important role. Furthermore, adaptations led to a decrease in challenge in Wiiski, which might limit the effectiveness of the game as a balance-training tool.